Assessment of the role of hydrogen to produce high-temperature heat in the steel industry. (15th February 2023) - Marocco, Paolo; Gandiglio, Marta; Audisio, Davide; Santarelli, Massimo
Abstract: The iron and steel industry is a major source of industrial greenhouse gas emissions, accounting for 7–9% of global energy-related CO2 emissions. Current steel production routes are therefore expected to undergo a profound decarbonisation process in the coming decades. This work aims to shed light on the role of hydrogen in decarbonising the supply of high-temperature heat in the steel sector by means of an optimisation framework. The model includes on-site hydrogen production using a low-temperature electrolyser integrated with a compression and storage system and gas burners, which can be fed with hydrogen and/or natural gas to cover the process heat demand. The assessment also takes advantage of real thermal load profiles of a scrap-based electric arc furnace steel plant. A sensitivity analysis is conducted on the electricity, natural gas and carbon prices. Cost-optimal maps are then derived to unveil the combination of energy and carbon prices at which hydrogen becomes convenient for heat production in the steel industry. A general relationship to define the cost-effectiveness of hydrogen is also given. The results show that, at current carbon prices (about 100 €/tCO2 ), the use of hydrogen becomes economically convenient when the electricity price is less than 0.4–0.6 times the natural gas price. In scenarios with electricity prices lower than about 0.10 €/kWh, as could occur with on-site renewable electricity generation, hydrogen cost falls below 6.5 €/kgH2, leading to cost savings of up to 60–70% compared to a natural gas-based configuration. Finally, when total CO2 emissions (direct + indirect) are considered, hydrogen becomes environmentally beneficial if the electricity carbon intensity is below 123 gCO2 /kWh.